PENEGAKAN HUKUM LINGKUNGAN DALAM BIDANG PENGELOLAAN SAMPAH SEBAGAI PERWUJUDAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE DI KOTA PAREPARE - wahyu; Hidayat, Asrul (FAKULTAS HUKUM UM PAREPARE, 2019)
This research is a research that aims to find out the application of the principle of good investment governance in the field of waste management in the city of Parepare. Knowing the role of the government, related agencies and the community in applying that principle.So that the principle of good investment governance can be achieved in accordance with the aims and objectives of the principle.This research is based on the incorporation of normative research with legislation related to this study. Some laws and also regional regulations. The legal materials used based on the research approach are primary legal material, Secondary legal materials,and Tertiary legal materials. While data analysis is used, namely collecting data from library data and interview results using a qualitative-descriptive approach.The results of the study can be concluded, first in the city of Parepare the rules on waste are contained in the field of regulation based on national and regional tierakat regulations, these regulations include: Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia, Law Number 32 of 2004 concerning Regional Government revoked by Law Number 23 of 2014 concerning Regional Government, Law No. 32 of 2009 concerning Environmental Protection and Management, Law No 18 of 2008 concerning Waste Management, Regional Regulation of the Municipality of Parepare Number 11 of 2012 concerning Waste Management. Second, elements of the Elements in the principle of Good Environmental Governance can be a reference by the government and the community in waste management in efforts to enforce preventive and repressive environmental law in waste management namely community empowerment, transparency, democratic decentralization, recognition of limited power support ecosystems and sustainability, Recognition of the rights of indigenous peoples and local communities, Enforceability.